Answer:
![y=3^x+10](https://img.qammunity.org/2021/formulas/mathematics/college/odm9oxer6k6rb2a48zb6pjg4am9qhw7jkf.png)
f(x)-values
decreased by 4
(4,87)
Explanation:
The table shows the exponential growth function
![y=a\cdot b^x +c](https://img.qammunity.org/2021/formulas/mathematics/college/chckzzja4hhfj6t9niw8vojlwrj3upje1j.png)
substitute some values to find
![a,b,c:](https://img.qammunity.org/2021/formulas/mathematics/college/6yxrjmy42fcgxjpgj9hjkdgag7no7n028p.png)
![13=a\cdot b^1+c\\ \\19=a\cdot b^2 +c\\ \\37=a\cdot b^3+c](https://img.qammunity.org/2021/formulas/mathematics/college/4lpu4sr1h2h31jeub35ss7fk03biuzh788.png)
Subtract these equations:
![ab^2+c-ab-c=19-13\Rightarrow ab(b-1)=6\\ \\ab^3+c-ab^2-c=37-19\Rightarrow ab^2(b-1)=18](https://img.qammunity.org/2021/formulas/mathematics/college/dremsfyklx1q817rj5e83wm4xeltwinfhr.png)
Divide them:
![(ab^2(b-1))/(ab(b-1))=(18)/(6)\Rightarrow b=3](https://img.qammunity.org/2021/formulas/mathematics/college/giq66co9cemip0y9bzj11m9qdbdks6smbc.png)
Then
![3a(3-1)=6\Rightarrow a=1](https://img.qammunity.org/2021/formulas/mathematics/college/pzta87pbaueb5h74c446mv5os1rkmqnu0x.png)
Hence,
![13=1\cdot 3+c\Rightarrow c=10](https://img.qammunity.org/2021/formulas/mathematics/college/xz1ysktakwlp8wijsuqbxix0kv6zpmcbym.png)
Therefore, the parent function is
![y=3^x+10](https://img.qammunity.org/2021/formulas/mathematics/college/odm9oxer6k6rb2a48zb6pjg4am9qhw7jkf.png)
If this function would be translated 4 units down, its expression will be
![y=3^x+10-4\\ \\y=3^x+6](https://img.qammunity.org/2021/formulas/mathematics/college/nqfkozs8fw9ilgjt7ufqmu2vwxavnxl2bu.png)
This means that f(x)-values decreased by 4.
Then the table for translated function is
![\begin{array}{cccccc}x&1&2&3&4&5\\ \\f(x)&9&15&33&87&249\end{array}](https://img.qammunity.org/2021/formulas/mathematics/college/fsf24szd388whu4h6lzq6vf6fzq734it7y.png)
The graph of translated function passes through the point (4,87)